Anxiolysis in the Surgical Management of a Compound Odontoma in a Pediatric Patient. (2nd April 2019) - Poli, Pier Paolo; Creminelli, Luca; Grecchi, Emma; Pieriboni, Silvia; Menozzi, Gregorio; Maiorana, Carlo
Abstract : Among odontogenic tumors, odontoma is the most frequent. The common treatment contemplates a conservative approach. While this procedure is generally accepted and tolerated, some difficulties may be encountered in the case of pediatric patients. Indeed, negative feelings of tension, apprehension, nervousness, and fear are likely to occur. The present report is aimed at discussing the management of a compound odontoma in a pediatric patient under anxiolysis with diazepam on an outpatient basis. The surgery was carried out without complications, and the discharge was completed safely. Oral premedication with diazepam should be considered to avoid more invasive sedation procedures in anxious pediatric patients.